2003
DOI: 10.4049/jimmunol.170.10.5219
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages RestrictPseudomonas aeruginosaGrowth, Regulate Polymorphonuclear Neutrophil Influx, and Balance Pro- and Anti-Inflammatory Cytokines in BALB/c Mice

Abstract: The role of macrophages in Pseudomonas aeruginosa corneal infection in susceptible (cornea perforates), C57BL/6 (B6) vs resistant (cornea heals), BALB/c mice was tested by depleting macrophages using subconjunctival injections of clodronate-containing liposomes before corneal infection. Both groups of inbred mice treated with clodronate-liposomes compared with PBS-liposomes (controls) exhibited more severe disease. In B6 mice, the cornea perforated and the eye became extremely shrunken, whereas in BALB/c mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 44 publications
6
64
0
Order By: Relevance
“…1A), consistent with previous reports demonstrating that BALB/c mice are more resistant to PAO1 infection (24)(25)(26). Interestingly, a comparison of BALB/c and BALB/c CD1d Ϫ/Ϫ mice revealed that BALB/c CD1d Ϫ/Ϫ mice were impaired in their ability to clear PAO1 from the lungs; a comparison of B6 to B6 CD1d Ϫ/Ϫ and B6 JA18 Ϫ/Ϫ mice revealed no such impairment (Fig.…”
Section: Resultssupporting
confidence: 79%
“…1A), consistent with previous reports demonstrating that BALB/c mice are more resistant to PAO1 infection (24)(25)(26). Interestingly, a comparison of BALB/c and BALB/c CD1d Ϫ/Ϫ mice revealed that BALB/c CD1d Ϫ/Ϫ mice were impaired in their ability to clear PAO1 from the lungs; a comparison of B6 to B6 CD1d Ϫ/Ϫ and B6 JA18 Ϫ/Ϫ mice revealed no such impairment (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Data from our in vivo experiments revealed through MPO assay that PMN numbers were reduced in the cornea of rVIP-treated vs PBStreated mice after 3 and 5 days p.i. Previous studies by this laboratory suggest that M play a major role in regulating the influx and persistence of PMN in the cornea (24). Delgado and Ganea (31, 32) also have shown that VIP inhibits the production of MIP-2, a potent chemoattractant for PMN, by BALB/c-derived M .…”
Section: Discussionmentioning
confidence: 71%
“…It is of interest to note that not only were BALB/c-derived M more sensitive to the lower concentrations of rVIP (10 Ϫ10 /10 Ϫ9 vs 10 Ϫ8 M) compared with B6, but when stimulated with LPS alone, BALB/c M also displayed a significantly more robust response than B6 via proinflammatory cytokine/chemokine production of both IL-1␤ and MIP-2. It has been reported by this laboratory that depletion of the M in both BALB/c and B6 mouse strains before ocular infection with P. aeruginosa results in an exacerbated disease response, suggesting that M play a key role in regulating/balancing pro-and antiinflammatory activity in the resistant and susceptible models (24). Previous studies also have also suggested that M from Th1 T cell responder mouse strains (B6) are different regarding functional behavior (phagocytic activity, NO generation) when compared with those from Th2 strains (BALB/c) (26,27).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Activation of TLR signaling initiates a variety of inflammatory events, such as infiltration of inflammatory cells (e.g., polymorphonuclear neutrophils [PMNs] and monocytes/macrophages) (13,20,21,27), as well as the production of inflammatory cytokines (e.g., tumor necrosis factor alpha [TNF-␣], macrophage inflammatory protein 2 [MIP-2], interleukin-1␤ [IL-1␤], gamma interferon [IFN-␥], IL-6, and IL-12) (12,22). In bacterial keratitis, the TLR-induced inflammatory mediators promote bacteria clearance and induce tissue repair; however, if unbalanced or uncontrolled, they may amplify the host inflammatory response, leading to tissue damage and corneal perforation (12,24).…”
mentioning
confidence: 99%